2005
DOI: 10.1081/clt-200066053
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Interactions of Rofecoxib with Lisinopril in Spontaneously Hypertensive Rats

Abstract: These results indicate that COX-2 inhibitors should be used judiciously in patients with history of hypertension, ischemic heart disease, or chronic renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Another COX-2 inhibitor, rofecoxib, caused an increase in blood pressure dependent on PGI 2 synthesis in normotensive Wistar-Kyoto rats (WKYs) and young spontaneously hypertensive rats (SHRs) fed a normal-salt or high-salt diet (Hocherl et al 2002 ). Rofecoxib also completely prevented the hypotensive effects of the ACEi inhibitor lisinopril in SHRs (Ricciotti et al 2018 ; Dubey et al 2005 ). Most importantly, clinical studies suggest that hypertension was more common in patients taking COX-2 inhibitors such as celecoxib and etoricoxib, and COX inhibition may attenuate the effects of some antihypertensive therapeutics (Mitchell et al 2020 ; Chan et al 2009 ).…”
Section: The Protective Role and Mechanism Of Cox-2 In Cardiovascular Diseasementioning
confidence: 99%
“…Another COX-2 inhibitor, rofecoxib, caused an increase in blood pressure dependent on PGI 2 synthesis in normotensive Wistar-Kyoto rats (WKYs) and young spontaneously hypertensive rats (SHRs) fed a normal-salt or high-salt diet (Hocherl et al 2002 ). Rofecoxib also completely prevented the hypotensive effects of the ACEi inhibitor lisinopril in SHRs (Ricciotti et al 2018 ; Dubey et al 2005 ). Most importantly, clinical studies suggest that hypertension was more common in patients taking COX-2 inhibitors such as celecoxib and etoricoxib, and COX inhibition may attenuate the effects of some antihypertensive therapeutics (Mitchell et al 2020 ; Chan et al 2009 ).…”
Section: The Protective Role and Mechanism Of Cox-2 In Cardiovascular Diseasementioning
confidence: 99%
“…9 Captopril and zofenopril with their sulfhydrylic group maintain a cardiovascular (CV) protective effect even in the presence of cyclooxygenase inhibitors differentially to enalapril, 9 ramipril, 10 or lisinopril. 11 Sulfhydryl ACE inhibitors might have a cardioprotective mechanism of action, which only in part includes a prostaglandin-mediated mechanism. In the Valsartan in Acute Myocardial Infarction (VALIANT) study in which 92% patients were treated with aspirin or other antiplatelet agents, captopril had similar outcomes than valsartan or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been reported on the interaction between ACE inhibitors and NSAIDs [5][6][7][8][9][10][11]. Likewise, there are number of possible drug interactions of lisinopril with NSAIDs [12][13][14][15].The study of potential drug interactions of lisinopril with various NSAIDs requires the quantitation of both of these drugs in various samples containing both of these types of drugs. A number of RP-HPLC methods are reported for the determination of lisinopril in dosage forms and spiked human plasma through derivatization [16] and in human plasma with fluorescence detection [17].…”
Section: Introductionmentioning
confidence: 99%